Identifying non-linear ground deformation trendsin Bucharest based on InSAR - Iuliana Armas; Mendes, D. A.; Popa, R.G.; Mihaela Gheorghe (9th INTERNATIONAL CONFERENCE ON GEOMORPHOLOGY (9th ICG), 2017)
In geomorphological literature there are numerous research papers on the nonlinear dynamics of the evolution of geomorphological systems. However, internationally, the modeling of the non-linearity of ground dynamics remained more at the level of theoretical models, lacking until now the technical support that provides the necessary data frame for concrete modeling. Synthetic Aperture Radar Interferometry technique proves to be a solution for overcoming lack of adequate data, through precise and repetitive measurements over large areas, especially in urban areas subject to a high density of coherent points in time. The proposed interferometry methods are Permanent Scatterers and Small Baseline Subset, which are both multi-temporal techniques capable to depict millimetre-level movements between two passes of the satellite. Regarding the capacity of studying ground dynamic patterns, the difference between PS and SBAS is that the SBAS is able to identify non-linearity in ground surface evolution, by using cubic or even quadratic models, while the PS method only depicts linearity. The SBAS highly correlated areas in time that help derive the deformation signal from multi-looked interferograms. PS looks at movement of discrete points, coherent in time, that are usually man-made objects. The research focusing on Bucharest capital city of Romania was based on SAR data acquired between 1992 and 2014 by ERS-1/-2, ENVISAT, and TerraSAR-X satellites, applying both, Small Baseline Subset (SBAS) and persistent scatterers (PS) high-resolution multi-temporal interferometry (InSAR) techniques, to provide maps of line-of-sight displacements.The recent SAR imagery was validated using terrestrial monitoring techniques. A wealth of statistical and numerical tests was employed on SBAS to find evidence of nonlinear dynamics and asymptotic attractors. Trends based on the estimated ground displacement in Bucharest are characterised by long-term memory, indicated by low noise Hurst exponents, which in the long-term form interesting attractors. We hypothesize these attractors to be an active northwest-southeast oriented transpressional system. Raportate la perioadeîndelungate de